An Oomycete CRN Effector Reprograms Expression of Plant HSP Genes by Targeting their Promoters. - Tianqiao Song (PLoS Pathogens, 2015)
Oomycete pathogens produce a large number of CRN effectors to manipulate plant immune responses and promote infection. However, their functional mechanisms are largely unknown. Here, we identified a Phytophthora sojae CRN effector PsCRN108 which contains a putative DNA-binding helix-hairpin-helix (HhH) motif and acts in the plant cell nucleus. Silencing of the PsCRN108 gene reduced P. sojae virulence to soybean, while expression of the gene in Nicotiana benthamiana and Arabidopsis thaliana enhanced plant susceptibility to P. capsici. Moreover, PsCRN108 could inhibit expression of HSP genes in A. thaliana, N. benthamiana and soybean. Both the HhH motif and nuclear localization signal of this effector were required for its contribution to virulence and its suppression of HSP gene expression. Furthermore, we found that PsCRN108 targeted HSP promoters in an HSE- and HhH motif-dependent manner. PsCRN108 could inhibit the association of the HSE with the plant heat shock transcription factor AtHsfA1a, which initializes HSP gene expression in response to stress. Therefore, our data support a role for PsCRN108 as a nucleomodulin in down-regulating the expression of plant defense-related genes by directly targeting specific plant promoters.